Advertising as A Marketing Communication - Rizki, Ayu Mulyana (International Research Journal of Management, IT & Social Sciences, 2015)
Theoretically delivering the concept and design of marketing and management, serving our clients with the most innovative techniques and ideas essential in todayâs competitive market for the success of any brand or product. At Abstract, we believe in superior customer service that is second to none, creating an unforgettable brand value with cutting-edge solutions and connecting your products to the right audience. Advertising as a marketing communication. The most basic concept underlying marketing is a human need. With the changing times, the need developed into a desire to consume a product with certain characteristics. Definition of marketing according to Kotler (2002, 10) marketing is a social process with the process of individuals and groups obtain what they need and want by creating, offering and freely exchanging goods and services of value with others.